The dual-defect passivation role of lithium bromide doping in reducing the nonradiative loss in CsPbX3 (X = Br and I) quantum dots. Issue 3 (24th November 2020) - Wu, Hao; Qiu, Jianbei; Wang, Jing; Wen, Yugeng; Wang, Qi; Long, Zhangwen; Zhou, Dacheng; Yang, Yong; Wang, Dazhao
Abstract : Lithium bromide as a new duel-defect passivation agent can effectively enhance luminescence properties by reducing the non-radiative loss. Abstract : The non-radiative loss in a perovskite, mainly resulting from thermal defects and halogen vacancies, has always been an important factor affecting its luminescence properties. The addition of a lithium ion has been demonstrated to be an effective way to reduce the nonradiative recombination in perovskite films, mainly acting on the surface/interface of the films. However, few studies have focused on its role in colloidal quantum dots. Herein, we have used LiBr as a new dual-defect passivation agent in colloidal CsPbX3 (X = Br and I) quantum dots to reduce the capture ability of the defects for excited electrons, leading to an effective reduction of the non-radiative recombination. The mechanism of LiBr doping in CsPbX3 (X = Br and I) quantum dots was studied by exploring its photodynamic process at room temperature and low temperature. Our results show that an appropriate concentration of LiBr can not only passivate the halide vacancy and thermal defect to reduce the nonradiative recombination, but also improve the phase stability caused by halide migration.